A New Species of Chigger in the Genius Siseca - Brown, Wayne A. (Silliman Journal, 2023)
Siseca gigarara n. sp. is described from specimens collected off a lizard host, Brachymeles schadenbergi, on Camiguin Island, Mindanao, Philippines. The genus is rediagnosed and comments on the genus are provided.